EFFECT OF SOME CHEMICAL ELICITORS ON SOME SECONDARY METABOLITE INDUCTION OF CORDIA MYXA L. IN VITRO - alaa jabbar taha (Journal of Global Pharma Technology, 2017)
Cordia myxa a tree belongs to boraginaceae family contained many secondary products like Flavonoids and Alkaloids. So uses as anti - inflammation, and antibacterial .The objective of this research to increase some secondary products from callus extraction by using chemical elicitors, like ZnSo4 and CoCl2 in various concentration, the method of Budhiraja was use to estimate the concentration of secondary products. Results showed that 0.5mg/l from ZnSo4 lead to significant increase compound dihydroxyrobmetin, Rubinin, and Chlorogenic reaching 2.95, 218.44, 60.99, µg/ml respectively. Moreover, had 2.5mg/l of ZnSo4 concentration negative impact on concentration of secondary metabolites, all compound decreased except datiscoside that arrived to highest rates significantly 70.63 µg/ml. While treatment 0.5 mg/l CoCl2 lead to decrease all compounds except hesperdin, which was significantly increase to 71.42 µg/ml, the concluded of this research showed that 0.5mg/l of CoCl2 and 2.5mg/l of Zno4 had negative effect on most concentration of secondary metabolites.